Mail order brides in modern America : a critical analysis of tafficked brides in public perception - Oschwald, Martha (2013)
Mail order brides are sometimes referred to as ‘trafficked brides’ because of the similar exploitation they and other human trafficking victims face. Though these women give their consent to immigrate for the purpose of becoming someone’s bride, often times they are unaware of the dangers involved and may end up in abusive or even deadly situations without appropriate knowledge or support. In addition, many mail order brides opt for this life-changing decision in spite of risks because of difficult circumstances they face in their countries of origin such as poverty, unrealistic parenting options or a low quality of life. In this thesis, I will explore the status of mail order brides in the United States at the time of Anastasia King’s murder trial in 2002 compared to recent public perception described by empirical analysis of well read American newspaper articles. I will further make the case that mail order brides deserve recognition under the wider umbrella of human trafficking as women facing considerable exploitation in a profit-minded and scarcely regulated industry.